Impact of TP53 gene variants on prognosis and survival of childhood acute lymphoblastic leukemia. (2nd May 2023) - Firtina, Sinem; Erbilgin, Yucel; Hatirnaz Ng, Ozden; Karaman, Serap; Karakas, Zeynep; Celkan, Tulin Tiraje; Gelen, Sema Aylan; Yildirmak, Yildiz; Ozbek, Ugur; Sayitoglu, Muge
Abstract: The tumor suppressor protein 53 ( TP53 ) gene is one of the most studied genes in cancer. Although TP53 variants are rare events in acute leukemia, recent observations showed that relapse samples might harbor TP53 variants. Here, we aimed to determine TP53 variants (hotspot region, exon 4–11) in childhood acute lymphoblastic leukemia (B and T-ALL) patients ( n  = 94) including diagnostic-relapse pairs ( n  = 15) by amplicon sequencing and evaluate the clinical impact of these variants. In total, nine different (E298*, R283C, R273H, L252F, C229F, I195T, E286G, c.955_956insC, and c.920-1G > C) variants were identified in 17 (18%) childhood ALL patients. c.(920-1G> C) splice site variant and c.(955_956insC) insertion were reported for the first time. In diagnose-relapse pair samples, we identified acquired and/or loss of TP53 variants in the samples at the time of relapse. TP53 variants were found to be more common in T-ALL (37%) than in B-ALL patients (9%). Pathogenic TP53 variants were associated with a shorter overall survival time ( p =  0.001). TP53 variants were found to be associated with inferior outcomes in our cohort and can be an independent risk factor for poor prognosis in childhood acute leukemia patients. Identification of low-frequent variants with next-generation sequencing approaches enables better knowledge of the clonal dynamics of ALL.